Peran Guru Dalam Membina Karakter Peduli Lingkungan Siswa pada Program Pasukan Semut (Sejenak Memungut) Sampah di Sekolah Alam Pacitan - Burhanuddin, Afid; Azizah, Fivian Prameswari; Erviana, Lina (IBTIDA-Jurnal Kajian Pendidikan Dasar, 2025)
This study aims to: (1) describe the implementation of the SEMUT (Sejenak Memungut/Briefly Picking Up) Waste Collection Program at Sekolah Alam Pacitan; and (2) describe the role of teachers in fostering students’ environmental care character through the program. The research employed a descriptive qualitative approach, with data sources consisting of first to third-grade teachers and selected third-grade students at Sekolah Alam Pacitan. Data were collected through interviews, observations, and documentation, with data credibility ensured through source and technique triangulation. Data analysis involved data reduction, data display, and conclusion drawing. The findings reveal that the SEMUT Program has been implemented in accordance with its components and indicators, including planning, implementation, and evaluation stages. However, community participation levels still require improvement. The teacher, as an educator, serves as a role model by consistently demonstrating proper waste disposal and management habits. The teacher provides appreciation for students' efforts as a form of motivation. As a guide, the teacher shows commitment by initiating activities that reduce the use of single-use items. The teacher trains students by involving them in hands-on practices. Acting as a facilitator, the teacher provides space for skill development through innovative project-based activities aligned with the principles of 5R (Reduce, Reuse, Recycle, Replant, Replace).